Weak acid and pepsin reflux induce laryngopharyngeal mucosal barrier injury: A rabbit-model-based study. - Chenjie Hou; Liqun Zhou; Yujin Zheng; Ting Chen; Renyou Hu; Jingyi Zheng; Chaofeng Liu; Yaqi Liu (PLoS ONE)
Objective Using rabbit models, this study simulated the laryngopharynx's response to the synergistic effects of various acidic reflux environments and pepsin to investigate the response mechanism underlying weak acid reflux and pepsin in the mucosal barrier injury of laryngopharyngeal reflux. Methods The rabbits were divided into six groups, and the original larynx was recorded for each group. During the study period, rabbits were sprayed with different doses of acid and pepsin solutions and monitored for hypopharyngeal mucosal transient impedance before and after modeling. After the experiment, laryngeal mucosal tissues were collected, observed using hematoxylin and eosin staining, and assessed for E-cadherin expression. The width of the intercellular space and lanthanum staining penetrating the intercellular space were also observed using electron microscopy. Results Eight weeks post-modeling, evidence of laryngopharyngeal mucosa inflammatory responses was observed in each group. Downregulation of E-cadherin expression significantly positively correlated with acid strength (p < 0.05). The pepsin and acid intervention groups showed a significantly widened space between mucosal epithelial cells in the posterior ring area (p < 0.05). Meanwhile, in the experimental group, a large amount of stained lanthanum penetrated the intercellular spaces; however, no significant difference was observed in the mucosal impedance (MI). Conclusion This study demonstrated that acid, weak acid, and pepsin could damage the laryngeal mucosal barrier; pepsin was an independent factor associated with tissue damage; the downregulation of hypopharyngeal cadherin was associated with acid-intensity exposure. Transient LP-MI cannot be applied directly.